السندات المثبتة للملكية العقارية الخاصة في التشريع الجزائري - حضري, مريم (جامعة الوادي University of Eloued, 2017)
نظرا لكون الملكية العقارية موضوعا هام، قام المشرع الجزائري بتحصينها، حيث أصدر قانون التوثيق الذي جاء بالسندات الرسمية كوسيلة لإثبات الملكية العقارية الخاصة، والقضاء على مخلفات الأوراق العرفية، لإحتمال خضوعها للتدليس والتزوير، وكأدوات جديدة لتنفيذ السياسة العقارية للدولة تضمن الملكية العقارية الخاصة وتحرير المعاملات العقارية فيها، قام أيضا باستحداث الغرف العقارية على مستوى المحكمة العليا وغيرها من القوانين لضمان استقراره. و لأنها من أهم المواضيع و أكثرها تعقيدا كون العقار في وقتنا الحالي أصبح أهم شيء لأنه أساس كل شيء، عمل المشرع على تنظيمها بقوانين تكون بمثابة الحصن المنيع و وسيلة ردع للأفراد لحماية الحقوق و تجنب نشوب أي نزاعات، بمعنى أصح تنظيم الوعاء العقاري و استقرار المعاملات العقارية، لكنها لم تكن كافية لتنظيم العقار حيث أن الملكية العقارية الخاصة أصبحت مطلبا اجتماعيا الكل يسعى وراء كسبها، باعتبار العقار أحد أهم الثروات للدولة لما يحتويه هو الآخر من ثروات سطحية و باطنية، و ذلك لأن جل المعاملات تكون لها علاقة بالعقار و ما لذلك من أهمية على دخل البلاد، فهو أموال عقارية، و هو مصدر الاستثمار الآن. Real Estate Property is an important subject that the Algerian legislator has fortified. The law of authentication, issued in official bonds, was issued as a means of proving private property ownership, eliminating the remnants of customary papers for possible fraud and counterfeiting, and as new tools for the implementation of real estate policy. He has also created real estate chambers at the level of the Supreme Court and other laws to ensure its stability. And because it is one of the most important and complex topics, because the real estate is now the most important thing because it is the basis of everything, the legislator has organized laws that act as a fortified fortress and a deterrent to individuals to protect rights and avoid any conflicts, But it was not enough to organize the real estate, since private property ownership became a social demand, all seeking to win it, considering that the property is one of the most important wealth of the state because it contains the other of the superficial and underground wealth, because most transactions have to do with the property and what Importance of the income of the country, it is a nation Real estate, and is the source of investment now
قانون عقاري
Keywords: الأثبات – السندات- الملكية – العقار; Proof - Bond - Property - Property.